Kaidah Mufrad dan Jama’ dalam Menafsirkan Al-Qur’an - Almunawar, Abdul Wahab; Islamiyah, Islamiyah; Setyawan, Rahmad; Qatrunnada, Salsabila; Afrianto, Rendi; Fiy, Muhammad Shun Fan'Ulum; siswanto, ahmad (STAI Syubbanul Wathon Magelang, 2024)
Abstract: The language and style of the Qur'ān have attracted a large number of Western Qur'ānic scholars. In looking at the substance of the Qur'anic uslub, it is necessary to approach the rules of interpretation such as mufrad and jama'. Mufrad and Jama' is one of the rules of interpretation that has uniqueness, because there are words that are consistently mufrad and jama'. This type of research is library research that explores the treasures of the ulumul Qur'an related to mufrad and jama'. This research uses the theoretical approach of the principles and ulumul Qur'an and tafsir. Primary data is taken from the literature of the main Qur'anic rules or ulum such as Manna Al-Qaththan. While secondary data is taken from various literature studies in the form of books, articles, and books of tafsir that have relevant to this paper. The results of this study are first, in terms of structure in Arabic grammar (ilm al-nahw, grammar), lafazh mufrad in Arabic means the same as singular in English, which means single. While the same lafazh jama' (English: plural) in English is a term used to refer to ism which indicates the meaning of more than two. Second, the use of mufrad in the Qur'an, for example, is Al-Ardh, Al-Nur, Al-Rih, Al-Nar and Al Jannah and the plural lafazh and its examples in the Qur'an include: al-sama', al-Rih.